A study on teacher’s obstacles in implementing the Kurikulum Merdeka at elementary school - Hasriani, Hasriani; Yanto, Yanto; Mayaputri, Velmi; Mahendra, Okta (Journal of Professional Teacher Education, 2024)
Indonesia adopts a curriculum called the Kurikulum Merdeka. The implementation of the Kurikulum Merdeka at State Elementary School Sukun faces significant challenges, particularly in limited resources, inadequate infrastructure, and the need for innovative teaching methods. This study employs a qualitative approach through interviews and documentation to gain an in-depth understanding of teachers' obstacles. Through descriptive and interpretive data analysis, researchers explore multiple perspectives, obtaining rich contextual insights. The findings indicate several barriers, including a lack of facilities, infrastructure, and guidebooks on the Kurikulum Merdeka. Teachers struggle due to the absence of these essential resources, hindering their ability to fully grasp and implement the curriculum effectively. Additionally, the school's remote location in Samparong Village exacerbates the issue, as the absence of a stable cellular network limits access to online learning resources. Despite these challenges, teachers strive to ensure students understand the lessons, although some still struggle with the new curriculum approach. To successfully implement the Kurikulum Merdeka, teachers must adopt creative teaching strategies to align with the Ministry of Education’s objectives. This study implied to the urgent need for comprehensive support, including guidebooks and infrastructure improvements, to enhance teachers' capacity in delivering effective learning experiences under the Kurikulum Merdeka.